Determination of l-norvaline and l-tryptophan in dietary supplements by nano-LC using an O-[2-(methacryloyloxy)-ethylcarbamoyl]-10,11-dihydroquinidine-silica hybrid monolithic column - Dongsheng Xu; Elena Sánchez-López; Qiqin Wang; Zhengjin Jiang; María Luisa Marina (Elsevier, 2020)
An analytical methodology based on an O-[2-(methacryloyloxy)-ethylcarbamoyl]-10,11-dihydroquinidine (MQD)-silica hybrid monolithic column was developed for the enantioseparation of 9-fluorenylmethoxycarbonyl (FMOC) derivatized amino acids by nano-liquid chromatography. The mobile phase was optimized including the apparent pH, content of ACN, and concentration of the buffer to obtain a satisfactory enantioresolution performance. 27 FMOC derivatized amino acids including 19 protein and 8 non-protein amino acids were tested, and 19 out of them were enantiomerically discriminated obtaining baseline separation for 11 of them. Analytical characteristics of the method were evaluated for norvaline and tryptophan in terms of linearity, precision, accuracy, limits of detection (LOD) and quantitation (LOQ) showing good performance to be applied to the enantiomeric determination of these amino acids in dietary supplements. LOD and LOQ values were 9.3 and 31 μM for norvaline enantiomers and 7.5 and 25 μM for tryptophan enantiomers, respectively. The contents of d-norvaline and d-tryptophan were below their respective LODs in all the analyzed samples. Quantitation of l-tryptophan and l-norvaline showed good agreement with the labeled contents except for one sample which did not show presence of l-norvaline, contrary to the label indication. Keywords: 9-Fluorenylmethoxycarbonyl, Amino acids, Chiral separation, Nano-LC, Quinidine-silica hybrid monolithic column